Digital Nomad Potential In Tetebatu Tourism Village: A Swot Analysis - Siti Hamdiah Rojabi; Adhitya Bagus Singandaru; Mahmudah Budiatiningsih; Muhammad Akbar Dio Sagita (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
The accelerated growth of remote work has precipitated a surge in digital nomadism, engendering novel opportunities for destinations that are conducive to supporting location-independent professionals. The present study employs a qualitative descriptive approach to examine the potential of Tetebatu tourism village in East Lombok, Indonesia, to develop as a rural digital nomad destination. The data presented herein was collected through a combination of semi-structured interviews with international visitors, field observations, and document analysis. The analysis was conducted utilizing a SWOT (Strengths, Weaknesses, Opportunities, Threats) framework. The findings indicate that Tetebatu possesses significant strengths, including scenic natural landscapes, cultural authenticity, community hospitality, and relatively stable internet connectivity. Nevertheless, structural limitations, including the absence of co-working spaces, limited English proficiency, inadequate transportation infrastructure, and national regulation (visa) constrain its implementation. Externally, the global rise of remote working and increasing demand for sustainable rural tourism present substantial opportunities, while competition from established hubs, environmental risks, and regulatory uncertainties remain key threats. This study contributes to the literature by extending the analysis of digital nomadism beyond an urban context and highlighting the role of rural destinations in the development of sustainable tourism.